2017
DOI: 10.3847/1538-4357/aa5cba
|View full text |Cite
|
Sign up to set email alerts
|

Charge States and FIP Bias of the Solar Wind from Coronal Holes, Active Regions, and Quiet Sun

Abstract: Connecting in-situ measured solar-wind plasma properties with typical regions on the Sun can provide an effective constraint and test to various solar wind models. We examine the statistical characteristics of the solar wind with an origin in different types of source regions. We find that the speed distribution of coronal hole (CH) wind is bimodal with the slow wind peaking at ∼400 km s −1 and a fast at ∼600 km s −1 . An anti-correlation between the solar wind speeds and the O 7+ /O 6+ ion ratio remains valid… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 70 publications
5
31
0
Order By: Relevance
“…Fe/O in the inverted HMF is significantly lower than in the slower wind behind, but is essentially the same as the faster wind ahead. For carbon and oxygen ion charge average states, the solar wind behind HMF inversions is significantly elevated relative to that ahead, as expected (Fu et al, 2017). Unlike the Fe/O, oxygen and carbon charge states in inverted HMF intervals are indistinguishable from the slower wind behind and significantly different from the faster wind ahead.…”
Section: Observations Of Inverted Hmfsupporting
confidence: 77%
“…Fe/O in the inverted HMF is significantly lower than in the slower wind behind, but is essentially the same as the faster wind ahead. For carbon and oxygen ion charge average states, the solar wind behind HMF inversions is significantly elevated relative to that ahead, as expected (Fu et al, 2017). Unlike the Fe/O, oxygen and carbon charge states in inverted HMF intervals are indistinguishable from the slower wind behind and significantly different from the faster wind ahead.…”
Section: Observations Of Inverted Hmfsupporting
confidence: 77%
“…A host of studies have linked in situ solar wind observations to active region (AR) sources (Kojima et al 1999;Neugebauer et al 2002;Culhane et al 2014;Fazakerley et al 2016;Kilpua et al 2016;Fu et al 2017). Neugebauer et al (2002) found AR-associated SW to exhibit moderately lower speeds, higher charge states, and greater variability in composition and plasma parameters than those from CHs; similarly to the slow wind.…”
Section: Active Regions As Solar Wind Sourcesmentioning
confidence: 99%
“…How the results change if the three types (CH, AR, and QS) solar wind are determined more restrictively? Usually the footpoints of the solar wind stay in a particular region for a few days (as shown in Figure 1 of Fu et al (2017)). A boundary wind is defined when the footpoint of the solar wind moves from one region to another (Neugebauer et al 2002).…”
Section: The Intervals Occupied By Interplanetary Coronal Mass Ejectimentioning
confidence: 99%